Factors Affecting Earning Management - Munasiron Miftah; Muhammad Daffa; Yudi Nur Supriadi (Garuda Prestasi Nusantara Consulting, 2025)
This study aims to examine the factors that affect profit management practices in 49 non-cyclical consumer sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. This research uses a quantitative approach by utilizing secondary data in the form of annual company reports. The analysis was carried out using the Fixed Effect Model (FEM) on the regression of panel data processed through STATA version 17 software. The results of testing and analysis show that financial distress has a negative effect on profit management, while leverage has a positive influence, while company size has no significant influence on profit management.